Mesenchymal stem cell preparations: comparing apples and oranges - Wagner, Wolfgang; Ho, Anthony Dick (Stem cell reviews, 2007)
Mesenchymal stem cells (MSC) represent a type of adult stem cells that can easily be isolated from various tissues and expanded in vitro. Past reports on their pluripotency and possible clinical applications have raised hopes and interest in MSC. Multiple designations have been given to different MSC preparations. So far MSC are poorly defined by a combination of physical, phenotypical and functional properties. As MSC could be derived from different tissues as starting material, by diverse isolation protocols, cultured and expanded in different media and conditions, the MSC preparations from different laboratories are highly heterogeneous. All of these variables might have implications (1) on the selection of cell types and the composition of heterogeneous subpopulations; (2) they can selectively favor expansion of different cell populations with totally different potentials; or (3) they might alter the long term fate of adult stem cells upon in vitro culture. The recent controversy on the multilineage differentiation potentials of some specific MSC preparations might be attributed to this lack of common standards. More precise molecular and cellular markers to define subsets of MSC and to standardize the protocols for expansion of MSC are urgently needed.